Glucocorticoids ameliorate TGF-β1-mediated epithelial-to-mesenchymal transition of airway epithelium through MAPK and Snail/Slug signaling pathways - Hyun-Woo Yang (Nature Portfolio, 2017)
Abstract Chronic rhinosinusitis with nasal polyps (CRSwNP) is closely associated with tissue remodeling. Epithelial-to-mesenchymal transition (EMT), a process of tissue remodeling, can be a therapeutic target of CRSwNP. Glucocorticoids are a type of steroid hormone that is used primarily in medical therapy for patients with CRSwNP; however, their effects on EMT in the airway epithelium remain unknown. To investigate the effects of dexamethasone and fluticasone propionate, a class of glucocorticoids, on transforming growth factor-β1 (TGF-β1) -induced EMT, we used A549 cells, human primary nasal epithelial cells (hPNECs) and ex vivo organ culture of the inferior turbinate. TGF-β1 induced changes in cell morphology, suppressed the expression of E-cadherin and enhanced the expression of a-smooth muscle actin, vimentin and fibronectin in A549 cells. However, glucocorticoids inhibited EMT, migration and invasion enhancement by TGF-β1. We found that the induction of phosphorylated ERK, p38 and the activity of Snail and Slug transcription factors by TGF-β1 were suppressed by glucocorticoids. Glucocorticoids also had a similar effect in hPNECs and ex vivo organ cultures of the inferior turbinate. These findings suggest that glucocorticoids might be a useful therapy for preventing tissue remodeling by blocking the EMT initiated by TGF-β1-induced MAPK and Snail/Slug signaling pathways in CRSwNP.